Issues of Strengthening the Economic Security of the Region - Rakhimov Eshmurad Normuradovich (Research Parks Publishers, 2022)
From a scientific, theoretical and practical point of view, the article reveals the issues of strengthening the economic security of the region, taking into account the tax potential. The results of scientific research in the field of strengthening the economic security of the region are summarized. The indicators of the development of Kashkadarya region are analyzed, on the basis of which conclusions concerning the problems of economic security are formed.